Production and structural characterization of solid lipid microparticles loaded with soybean protein hydrolysate. (October 2015) - Salvim, Mariana O.; Thomazini, Marcelo; Pelaquim, Fernanda P.; Urbano, Alexandre; Moraes, Izabel C.F.; Favaro-Trindade, Carmen S.
Abstract: The aims of this study were to produce and evaluate solid lipid microparticles (SLMs) loaded with soy protein hydrolysate (HP). The SLMs were produced by spray chilling with an active material and carrier ratio of 1:5 and 1:10 and in two feed preparations: emulsion and suspension. The rheological parameters of the feeds produced by emulsions were studied, morphological characteristics of the SLMs were examined via scanning electron microscopy (SEM) and confocal microscopy, the particle size and distribution were measured via laser light diffraction, and the structural properties of the SLMs were characterized via infrared (FTIR) spectroscopy and X-ray diffraction (XRD). SEM images showed that SLMs were spherical and agglomerated. The analysis of X-ray diffraction indicated that the microparticles after 90 days of storage had β polymorphic form. The preparation methods for feeds, emulsion and suspension, had no influence on the rheological parameters, and the median particle size of the SLMs and interactions between the ingredients were not detected via FTIR spectroscopy; however, the SLMs prepared by emulsion contained pores and had a higher incorporation efficiency of HP. The spray chilling technique is suitable method for microencapsulation of soy protein hydrolysate. So, this technique could be useful for attenuating HP unpleasant taste, for its protection and also for promoting its release in the intestine, during fat digestion. Highlights: This is the first paper where one hydrolysate was encapsulated by spray chilling. This study revealed the effect of feed preparation on its rheology. Atomizing of two different feed, emulsion and suspension Higher incorporation efficiency of SLM obtained by emulsion Atomizing of emulsion resulted in porous particles.